Mesenteric Panniculitis Presenting as Fever of Unknown Etiology in a Patient with History of Abdominal Surgery - Christopher P. Irwin; Joo B. Lee; Andrew Kim; Ijagha Eme; Christina Schofield; George Mount (Case Reports in Gastrointestinal Medicine)
Mesenteric panniculitis is characterized by nonspecific fibrous inflammation of the small bowel mesentery, appendix, and mesoappendix. Clinical course is usually benign and outcome is favorable. We report a case of mesenteric panniculitis presenting as fever of unknown etiology in a patient with history of abdominal surgery.